2020
DOI: 10.1080/02640414.2020.1823083
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the “gut instinct” of expert coaches during talent identification

Abstract: Coaches are an integral part of talent identification in sport and are often used as the "gold standard" against which scientific methods of talent identification are compared. However, their decision-making during this process is not well understood. In this article, we use an ecological approach to explore talent identification in combat sports. We interviewed twenty-four expert, international-level coaches from the Olympic disciplines of boxing, judo, and taekwondo (age: 48.7 + 7.5 years; experience: 20.8 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 53 publications
1
40
0
3
Order By: Relevance
“…This indicates that having a single coach evaluate multiple athletes is not an ideal scenario, as coaches are unable to form a consistent opinion of an athlete's talent that they are comfortable with. This finding supports previous research by Roberts et al (2020), who found that coaches require time to get to know athletes before forming a confident evaluation of the athlete's future sporting potential. In this study, although the coaches had 4 days in which to evaluate the athletes, it appears that the number of athletes inhibited the coaches' capacity to survey the athletes in as much detail as they would require to make confident judgments and decisions.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This indicates that having a single coach evaluate multiple athletes is not an ideal scenario, as coaches are unable to form a consistent opinion of an athlete's talent that they are comfortable with. This finding supports previous research by Roberts et al (2020), who found that coaches require time to get to know athletes before forming a confident evaluation of the athlete's future sporting potential. In this study, although the coaches had 4 days in which to evaluate the athletes, it appears that the number of athletes inhibited the coaches' capacity to survey the athletes in as much detail as they would require to make confident judgments and decisions.…”
Section: Discussionsupporting
confidence: 90%
“…For group analysis, rankings were used to sort athletes into three categories to conceptualize the talent identification process (Roberts et al, 2020). Therefore, the athlete rankings are presented in three groups -High ranking (athletes ranked from 1 to 8), medium ranking (9-16) and low ranking (17-24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These timelines present challenges for coaches to gather enough information to make informed decisions about whether or not an athlete has the skills necessary (presently) and can develop within the environment the coach creates (in the future). Thus, coaches can be forced to make decisions based on snap shots of athlete performance, and in turn, may rely on gut feeling and intuition 1 (Christensen, 2009 ; Jokuschies et al, 2017 ; Musculus and Lobinger, 2018 ; Roberts et al, 2021 ). Moreover, reduced resources could mean coaches are solely responsible for these selections without the support and guidance of other coaches and/or colleagues.…”
Section: Storm Clouds On the Horizon For Athlete Selectionmentioning
confidence: 99%